Nonlinear interactive source-filter models for speech. (March 2016) - Koc, Turgay; Ciloglu, Tolga
Abstract : Highlights: We propose two interactive source-filter models, ISFMs, for speech production. ISFMs have the capability of producing fine details of glottal flow. A parameter estimation method is developed for determining the model parameters. The algorithm yields ISFMs performing better than linear source-filter model. Abstract: The linear source-filter model of speech production assumes that the source of the speech sounds is independent of the filter. However, acoustic simulations based on the physical speech production models show that when the fundamental frequency of the source harmonics approaches the first formant of the vocal tract filter, the filter has significant effects on the source due to the nonlinear coupling between them. In this study, two interactive system models are proposed under the quasi steady Bernoulli flow and linear vocal tract assumptions. An algorithm is developed to estimate the model parameters. Glottal flow and the linear vocal tract parameters are found by conventional methods. Rosenberg model is used to synthesize the glottal waveform. A recursive optimization method is proposed to find the parameters of the interactive model. Finally, glottal flow produced by the nonlinear interactive system is computed. The experimental results show that the interactive system model produces fine details of glottal flow source accurately.